A rapid method for the determination of brominated flame retardant concentrations in plastics and textiles entering the waste stream. Issue 19 (28th August 2017) - Abdallah, Mohamed Abou‐Elwafa; Drage, Daniel S.; Sharkey, Martin; Berresheim, Harald; Harrad, Stuart
Abstract: Due to new European legislation, products going to waste are subject to 'low persistent organic pollutant concentration limits'. Concentrations of restricted brominated flame retardants in waste products must be determined. A rapid extraction and clean‐up method was developed for determination of brominated flame retardants in various plastics and textiles. The optimised method used vortexing and ultrasonication in dichloromethane followed by sulfuric acid clean‐up to determine target compounds. Poly‐brominated diphenyl ethers were determined by gas chromatography with mass spectrometry and hexabromocyclododecane by liquid chromatography with tandem mass spectrometry. Good recoveries of target analytes were obtained after three extraction cycles. The method was validated using poly‐propylene and poly‐ethylene certified reference materials as well as previously characterised textiles, expanded and extruded poly‐styrene samples. Measured concentrations of target compounds showed good agreement with the certified values indicating good accuracy and precision. Clean extracts provided low noise levels resulting in low limits of quantification (0.8–1.5 ng/g for poly‐brominated diphenyl ethers and 0.3 ng/g for α‐, β‐ and γ‐hexabromocyclododecane). The developed method was applied successfully to real consumer products entering the waste stream and it provided various advantages over traditional methods, including reduced analysis time, solvent consumption, minimal sample contamination and high sample throughput, which is crucial to comply with the implemented legislation.